2020
DOI: 10.1007/s40789-020-00303-6
|View full text |Cite|
|
Sign up to set email alerts
|

Petrology, physicochemical and thermal analyses of selected cretaceous coals from the Benue Trough Basin in Nigeria

Abstract: Abundant coal resources that were previously neglected due to a crude oil boom need revitalisation and integration into the national electricity mix to address the energy demands of the Nigerian population. Selected coal samples from the Benue Trough sedimentary basin in Nigeria were examined by various techniques, including proximate and ultimate analyses, organic petrography, Fourier transform infrared ray spectroscopy, and thermogravimetric analysis. Based on vitrinite reflectance, the Lafia-Obi (OLB), Gari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, the AKZ and OME samples examined in this study have similar fuel properties with other lignites from Obomkpa, Ihioma, and Ogboligbo (Nyakuma 2019;Nyakuma et al 2019a) and Subbituminous coals such as Owukpa and Garin Maiganga in Nigeria (Ryemshak and Jauro 2013;Nyakuma and Jauro 2016b;Akinyemi et al 2020a). Lignite is an essential fuel source in many countries, where it is utilised for the production of electric power (79%), synthetic natural gas (SNG) (13%), fertilizer (7%), along with heating homes and oil drilling (Lignite Energy Council 2020).…”
Section: Potential Applications and Future Outlooksupporting
confidence: 66%
See 2 more Smart Citations
“…Furthermore, the AKZ and OME samples examined in this study have similar fuel properties with other lignites from Obomkpa, Ihioma, and Ogboligbo (Nyakuma 2019;Nyakuma et al 2019a) and Subbituminous coals such as Owukpa and Garin Maiganga in Nigeria (Ryemshak and Jauro 2013;Nyakuma and Jauro 2016b;Akinyemi et al 2020a). Lignite is an essential fuel source in many countries, where it is utilised for the production of electric power (79%), synthetic natural gas (SNG) (13%), fertilizer (7%), along with heating homes and oil drilling (Lignite Energy Council 2020).…”
Section: Potential Applications and Future Outlooksupporting
confidence: 66%
“…Typically, the processing and utilisation of coal are hampered by high moisture content. In this study, the moisture content of below 10% observed for all the coal samples are within the acceptable limits for electric power generation or conversion into value-added products (Chukwu et al 2016;Akinyemi et al 2020a). In contrast, the volatile matter (VM) is an important factor for determining not only the coal rank but also its suitability for potential energy recovery from thermal processes such as combustion and pyrolysis (carbonisation) (Speight 2012;Nyakuma 2016).…”
Section: Kinetic Analysesmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, the outlined properties of coal provide insights into the thermal degradation behaviour, emissions profile, and potential environmental impact during energy recovery and electricity generation in power plants. However, the data on various Nigeria coals is limited to the geological, geochemical, petrographic, petrologic, sedimentology, and mineralogical properties as reported in the literature (Ayinla et al, 2017;Ogala, 2018;Akinyemi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined the source rock potentials (Akande et al 2007), mineralogy (Ogala et al 2012), petrology (Wuyep and Obaje 2012), sedimentology (Sonibare et al 2013), lithostratigraphy (Uzoegbu et al 2013), hydrocarbon potentials (Jauro et al 2014), geology (Ayinla et al 2017b), petrography (Ayinla et al 2017a), and geochemistry (Akinyemi et al 2020a) of selected Nigerian coals in the literature. Other studies have examined the physicochemical (Akinyemi et al 2020a), thermal conversion (Nyakuma et al 2016), major/trace elements (Sonibare et al 2013), and kinetic properties (Sonibare et al 2005) of selected coals from Nigeria. However, there are limited studies that comprehensively examine the fuel, material, and energetic characteristics of Nigerian coals particularly from the Benue trough where there have been numerous discoveries of large deposits in recent times.…”
Section: Introductionmentioning
confidence: 99%